Implementasi Ceklist Handover Untuk Meningkatkan Transfer Informasi Dalam Handover Intraoperatif : Literature Review - Kurnia, Esti Eva; Nursalam, Nursalam; Junait, Junait (Care : Jurnal Ilmiah Ilmu Kesehatan, 2024)
Communication failures in information transfer during intraoperative handover can pose a risk to patient safety incidents. One of the factors influencing the success of intraoperative handover is the existence of a structured handover checklist. This study aimed to explain the implementation of a structured intraoperative handover checklist to improve information transfer during intraoperative handovers. The design employed was a literature review. Articles were selected from databases including ScienceDirect, Scopus, PubMed, and Springer Link. The criteria for article selection included publication between 2017 and 2022, full text in English, and the use of keywords such as 'intraoperative handover,' 'handover checklist,' and 'information transfer.' The PRISMA flowchart stages were utilized to filter appropriate articles. The critical assessment of article quality employed The Joanna Briggs Critical Appraisal Tools 2020 and Mix Methods Appraisal Tool 2018. The results of the review of 8 articles indicated that a lack of good coordination during intraoperative handovers often occurs due to the absence of structured guidelines regarding handover content. The application of an intraoperative handover checklist has been shown to increase the completeness of data transfers and reduce the percentage of information omission during the handover process. The implementation of structured intraoperative handovers has a positive influence on improving the quality of communication between surgical teams and reducing incomplete information conveyed. A structured intraoperative handover checklist is needed as a guide to reduce the number of errors in information transfer, thus enhancing patient safety.